Understanding the Gap Between Nursing Workforce in the United States and Population Needs—A Policy Brief - Al Mohajer, Mayar (Avicenna Journal of Medicine, 2023)
Purpose This report is intended to analyze the root causes for the current gap between the nursing workforce and population needs in the United States. It aims to consolidate what is known about these contributing reasons and provide evidence-based recommendations for action.Methods The report utilized the Sample, Phenomenon of Interest, Design, Evaluation, Research type framework to develop the research question and the 5 Whys methodology for the root cause analysis.Results This report highlighted six major causative problems, including workforce market mismatch, poor financing design, inadequate governance, flawed technologies, insufficient research, and suboptimal service delivery. A detailed evaluation of root causes with supported evidence is presented.Conclusion The report provided seven actionable recommendations based on the analysis: (1) strengthening the nursing role in advancing equity, (2) investing in nursing well-being, (3) changing policies and payment structure, (4) including nursing in technology design, (5) strengthening nursing education, (6) developing a robust public health emergencies preparedness plan, and (7) investing in relevant research.
Keywords: nursing; policy; shortage